The nearby Galaxy structure toward the Vela Gum nebula - Giorgi, E. E. (2015)
We report on UBVI photometry and spectroscopy for MK classification purposes carried out in the fields of five open clusters projected against the Vela Gum in the Third Galactic Quadrant of the Galaxy. They are Ruprecht 20, Ruprecht 47, Ruprecht 60, NGC 2660 and NGC 2910. We could improve/confirm the parameters of these objects derived before. Ruprecht 20 is not a real physical entity, in agreement with earlier suggestions. Ruprecht 47, a young cluster in the Galactic plane, at 4.4 kpc from the Sun is quite farther than in previous distance estimations and becomes, therefore, a member of the Puppis OB2 association. For the first time Ruprecht 60 was surveyed in UBVI photometry. We found it to be placed at 4.2 kpc from the Sun of about and 1 Gyr old. NGC 2660 is another old object in our survey for which distance and age are coincident with previous findings. NGC 2910 turns out to be a young cluster of Vela OB1 association at a distance of 1.4 kpc approximately and 60 Myr old. The spectroscopic parallax method has been applied to several stars located in the fields of four out of the five clusters to get their distances and reddenings. With this method we found two blue stars in the field of NGC 2910 at distances that make them likely members of Vela OB1 too. Also, projected against the fields of Ruprecht 20 and Ruprecht 47 we have detected other young stars favoring not only the existence of Puppis OB1 and OB2 but conforming a young stellar group at ∼ 1 kpc from the Sun and extending for more than 6 kpc outward the Galaxy. If this is the case, there is a thickening of the thin Galactic disk of more than 300 pc at just 2-3 kpc from the Sun. Ruprecht 60 and NGC 2660 are too old objects that have no physical relation with the associations under discussion. An astonishing result has been the detection in the background of Ruprecht 47 of a young star at the impressive distance of 9.5 kpc from the Sun that could be a member of the innermost part of the Outer Arm. Another far young star in the field of NGC 2660, at near 6.0 kpc, may become a probable member of the Perseus Arm or of the inner part of the Local Arm. The distribution of young clusters and stars onto the Third Galactic Quadrant agrees with recent findings concerning the extension of the Local Arm as revealed by parallaxes of regions of star formation. We show evidences too that added to previous ones found by our group explain the thickening of the thin disk as a combination of flare and warp.